Penerapan Model Cooperatif Tipe Jigsaw Meningkatkan Hasil Belajar IPA pada Materi Pencernaan Pada Manusia dan Hewan Kelas V SDN 2 Kalisari - Wijaksono, Agus; Dharmawan, Yudhi; Mushoffa, Mushoffa (MUNAQASYAH : Jurnal Ilmu Pendidikan dan Pembelajaran, 2023)
The use of a jigsaw type cooperative learning approach to increase the science learning scores of fifth grade students at SD Negeri 2 Kalisari is the problem discussed in this research. The author teaches in class V at SD Negeri 2 Kalisari, students in this case have only reached 39%, based on the results of daily tests where the average score is 62. Even though the KKM chosen is 73, this shows that learning still needs to be improved. The jigsaw type cooperative learning methodology will be used to increase the scientific education value of class V students at SDN 2 Kalisari. He conducted a qualitative investigation of this problem using a research design with a class action perspective. Participants in this research were 18 class V students at SDN 2 Kalisari who were registered in the first semester of the 2023–2024 academic year, with a total of 11 boys and 7 girls. This shows how the jigsaw type cooperative learning paradigm has increased student learning scores in science. It has been proven that the jigsaw type cooperative learning model can improve the learning outcomes of fifth grade science students cooperatively